Correlation of Hepcidin with Some Biochemical Parameters in Iraqi Children with Growth Hormone Deficiency (Baghdad Science Journal, 2024)
Hepcidin (Hep.) is a protein that maintains iron balance in the body. The Information about the role of Hep. in pathophysiology that is associated with growth hormone deficiency (GHD) is scarce. This study evaluates the correlation of Hep. with some biochemical parameters: Growth Hormone (GH), Insulin-Like Factor-1 (IGF-1), Iron, Vitamin D, Alkaline Phosphatase (ALP), Calcium, Phosphorous, and Ferritin in growth hormone deficient children. Children with GHD (60) and healthy volunteers (60) participated in this study, and their serum samples are collected from National Diabetes Center- Almustansirya University from the period January to April 2022. Enzyme Linked Immune Sorbent Assay (ELIZA) is used to measure Hep. while Chemiluminescence immunoassay is to measure GH and IGF-1.Results demonstrate significant decrease of p<0.01 in the Hep. level in the sera of GHD patients when compared to healthy individuals, and iron levels increase. This can be explain the inverse relationship between hepcidin and iron .It is an important regulator of iron absorption, this mechanism through Hep. preventive any impact against anemia by increasing the bioavailability of (Fe). Therefore, this study is carried out to give a better understanding about the parameters that affect the children with GHD and Hep. that can be a dependable parameter for better management of those children.